Exploration of Potential Molecular Targets of Dexmedetomidine in the Intestinal Repair of Burnt Rats - Qin C; Jiang Y; Yu M; Bian Y; Yu Y (Dove Medical Press, 2021)
Chao Qin,1- 3 Yi Jiang,1,2 Mingdong Yu,1,2 Yingxue Bian,4 Yonghao Yu1,2 1Department of Anesthesiology, Tianjin Medical University General Hospital, Tianjin, 300052, People's Republic of China; 2Tianjin Institute of Anesthesiology, Tianjin, 300000, People's Republic of China; 3State Key Laboratory of Medicinal Chemical Biology (Nankai University), Tianjin, 300071, People's Republic of China; 4Department of Anesthesiology, Tianjin Union Medical Center, Tianjin, 300121, People's Republic of ChinaCorrespondence: Yonghao YuDepartment of Anesthesia, Tianjin Medical University General Hospital, No. 154 Anshan Road, Heping District, Tianjin, 300052, People's Republic of ChinaTel +86-13920590099Email yyu@tmu.edu.cnBackground: More and more burn survivors were suffering from varying degrees of damage to the intestinal barrier. Dexmedetomidine (Dex) was frequently used as sedative in more cases, but it was found to have repair effect on intestinal barrier dysfunction recently. This study aimed to explore the potential specific targets of Dex in intestinal barrier repair in burn rats model.Methods: Male adult SD rats were used to establish 40% TBSA III degree scald model in our study. The samples were divided into four groups: burn rats (Burn), burn rats with Dex medication (Burn-Dex), sham rats (Sham) and sham rats with Dex medication (Sham-Dex). And plasma FITC-dextran and diamine oxidase (DAO) were detected to determine the intestinal permeability. Differentially expressed proteins were further adopted to protein-protein interaction network analysis, Gene Ontology analysis (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis.Results: It showed that 40% TBSA III degree scald model was successfully constructed. And plasma FITC-dextran and DAO decreased significantly after Dex administration. Additionally, differentially expressed genes Psmb10, Psmb7 among the experimental groups were screened, which were significantly enriched in proteasome and other several pathways.Conclusion: The results above suggested that Q4KM35 and Q9JHW0, which are encoded by Psmb10 and Psmb7, respectively, are two possible protein targets of Dex in intestinal barrier repair.Keywords: dexmedetomidine, intestinal barrier, Psmb10, Psmb7